Permodelan Tsunami dan Implikasinya Terhadap Mitigasi Bencana di Kota Palu - Pratomo, Rahmat Aris; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
The City of Palu, Central Sulawesi is one of the regions in Indonesia which are vulnerable to tsunami and require a preventive action plan and mitigation to reduce potential risks. This study analyzed tsunami inundation zones and their implications regarding disaster mitigation in the city. This study employed quantitative approach using Geographical Information System (GIS) to map tsunami disaster prone areas. Cost Distance was used to model tsunami disaster; spatial analyst and network analyst were used to analyze the level of danger, vulnerability, and risk of tsunami, and also the establishment of evacuation routes. Analysis indicated the followings: (1) The City of Palu has large potential for tsunami inundation, (2) tsunami danger area comprises 9,63% of total city area, (3) tsunami vulnerable area 9,83% of total city area, (4) tsunami risk area 3,83% of total city area, and (5) there are 50 shelters acting as evacuation points and 108 evacuation routes in around the city. The built up area around the coast of Palu Bay area was identified as having high risk of tsunami disaster. Evacuation routes are scattered in the built up areas with the number of routes corresponding to population density.